2019
DOI: 10.1039/c9ob00336c
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-free α-Csp3–H oxidative sulfuration of benzyl thiosulfates with anilines to form N-aryl thioamides

Abstract: A transition metal-free synthesis of N-aryl thioamides was realized by the oxidative sulfuration of Bunte salts in DMSO with anilines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…After thorough optimization of reaction conditions, the reaction was conducted using CuI as the catalyst, DCE as the solvent, and oxygen as the green oxidant at 100 °C, the desired product 4a was isolated in 83% yield (Table , entry 1). It was noteworthy that sulfenylation of maleimides, thia-Michael addition of Bunte salt with maleimides, and α-amination of Bunte salt with amines were not observed at all during optimization of the reaction conditions. It was found that the choice of copper catalyst was a critical success factor for this reaction.…”
mentioning
confidence: 99%
“…After thorough optimization of reaction conditions, the reaction was conducted using CuI as the catalyst, DCE as the solvent, and oxygen as the green oxidant at 100 °C, the desired product 4a was isolated in 83% yield (Table , entry 1). It was noteworthy that sulfenylation of maleimides, thia-Michael addition of Bunte salt with maleimides, and α-amination of Bunte salt with amines were not observed at all during optimization of the reaction conditions. It was found that the choice of copper catalyst was a critical success factor for this reaction.…”
mentioning
confidence: 99%
“…This result demonstrated the first insight into the selective formation of the carbonyl compound 3a based on the amount of base. With this result in hand and considering 4 equivalents of NaOH as ideal for the formation of 3a, we then explored the influence of diverse solvents (Table 1, entries [12][13][14][15][16][17][18][19]. It can be observed that none of the tested solvents affected the reaction positively.…”
Section: Resultsmentioning
confidence: 99%
“…We next surveyed a range of differently substituted β-keto esters in the reaction with sodium S-benzyl sulfurothioate (2a, Table 2, entries [11][12][13][14][15][16][17][18]. This protocol enabled the synthesis of various α-benzylthio esters 3k-r bearing alkyl, allyl, and benzyl groups directly bonded to the oxygen atom of the ester group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation